Marilyn Monroe with Arthur Miller at press conference (Module II, 2013)
USA. Connecticut, Roxbury, Goldsmith Road. Marilyn Monroe and Arthur Miller attend a press conference. Miller talks about being hounded by press, and refuses to comment when asked by reporters why he refused to name names of Communist known to him during the McCarthy Trials. Monroe talks about whether she will continue her film career after her marriage to Miller.